CCTV Surveillance Systems and Their Impact on Traffic Compliance and Public Road Behavior in Goa - Naik, Gaurav Arvind; Varak, Shruti Vishnu; Karmalkar, Sharvari Alias Janvhi Hitendra Shet; Otawanekar, Sayee Hiren (International Journal of Computer Sciences and Engineering, 2025)
Traffic violations are a major cause of accidents and reduced traffic safety in Goa. CCTV cameras can enhance monitoring and enforcement. This study examines the link between public awareness, perceptions, and experiences with CCTV surveillance, and how these factors influence actual traffic behavior and support for further expansion. Data were collected through a structured public survey capturing demographic information, driving behaviors, and opinions on CCTV. Three hypotheses were tested using the chi-square test of independence: (1) the relationship between awareness of CCTV and rule compliance, (2) the relationship between perceived effectiveness of CCTV and support for expansion, and (3) the relationship between experiences of false fines and support for expansion. All hypotheses showed statistically significant relationships. Findings indicate that greater public awareness and belief in CCTV effectiveness led to higher compliance and stronger support for deployment. Conversely, negative experiences, such as false fines, reduce public support. The study concludes that public awareness campaigns, system accuracy, and concerns about privacy must be addressed to ensure successful CCTV implementation.